Dynamic interfacial bond behaviour between basalt fiber reinforced polymer sheets and concrete - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong; Cui, J.; Shi, Y. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
An experimental investigation on the dynamic interfacial bond behaviour between basalt fibre (BFRP) sheets and concrete under different loading speeds (i.e. 8.33E−6 m/s, 0.1 m/s, 1 m/s, 3 m/s, 5 m/s, and 8 m/s) by using single-lap shear tests was carried out in this study. Experimental results including bond strength, strain time histories, strain distributions in the bonding areas, interfacial fracture energy, and bond-slip curves are presented in this study. The test results show that the interface is strain rate dependent. The interfacial fracture energy, bond strength, and interfacial bond shear stress-slip are sensitive to strain rate. Empirical bond-slip model including strain rate effect are established for the predictions of bond properties between BFRP sheets and concrete under dynamic loading.